Maḥmūd Yūnus wa Ittijāhātuhu fī Tahdīd Ta‘līm al-lughah al-‘Arabīyah bi Indūnīsīyā - Didin Syafruddin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
Mahmud Yunus is one of the Indonesian students who was in Cairo in the thirties and is seen to have made a great contribution to the development of national Islamic education since the time of Indonesian independence. Having finished his studies at al-Azhar University 1927, Yunus studies at Darul Ulum to widden his intellectual horizon untul he obtained his certificate in 1930. As a graduate of one of the most important centers of Islamic learning, he had a lofty status in the Muslim community. Yunus served as a teacher in an Islamic teacher training school (Normal Islam), in padang, West Sumatra and later he was appointeed as a goverment official, seeking to establish and improve Islamic school in Indonesia. He was also a rector and professor of Islamic education at the State Institute of Islamic Studies in Padang.DOI: 10.15408/sdi.v2i3.831